(untitled) (Journal of the College of Education for Women, 2023)
This study examined the imperative construction: the command, the interrogative, the prohibition, the call, and the wish. In the Diwan of Al-Shamakh bin Dirar; where the poetic verses were monitored in each of the topics of the student’s creation, and the rhetorical meanings that he came out with. What is new in this study is that it is the first to study the demanded composition in the poetry of a glorious poet, Al-Shammakh bin Dirar Al-Dhubyani. As his poetry did not receive such a study, it sought to employ what was written by rhetoric scholars, in an attempt to explore the demanded composition in the poetry of Al-Shamakh. The study adopted the descriptive analytical approach, which is based on counting the number of times the poet used each of the methods of requesting composition, and analyzing the rhetorical contexts in which these methods were mentioned. The study included an introduction, a preface, and three topics. In the introduction, I dealt with the life of the poet, his poetry, his status, and the definition of composition and its types. As for the detectives; In it, I dealt with the request composition in the poet’s diwan, and the rhetorical meanings that came out to it.